Do stronger Anti Money Laundering (AML) measures reduce crime? An empirical study on corruption, bribery, and environmental crime - Agung Andiojaya (Journal of Economic Criminology)
The objective of anti-money laundering (AML) programs is to disrupt the financial infrastructure of criminal organizations, thereby seizing illicit assets and curbing the expansion of these criminal activities. This paper assesses the effectiveness of AML programs in curbing three distinct forms of criminal activity: corruption, bribery, and environmental crime. The analysis encompasses a representative sample of 192 countries. These crimes were selected due to their significant socio-economic impacts and their strong dependence on illicit financial flows. This study employs multivariate multiple regression analysis and multivariate analysis of variance (MANOVA) to assess the influence of money laundering risk on the Corruption Perception Index (CPI), bribery risk, and environmental crime. The results indicate that rigorous AML measures significantly mitigate the risks associated with these crimes, substantiating the hypothesis that efficacious AML programs can deter criminals by limiting access to illicit funds. This research addresses a gap by quantitatively assessing AML effectiveness across diverse criminal activities, contributing to the broader discourse on financial crime prevention.